Pelatihan Pengembangan Media Pembelajaran pada Guru MI Al Muhammady Mentoro Kecamatan Sumobito (Neolectura, 2021)
Training on Learning Media Development for MI Al Muhammady Mentoro Teachers, Sumobito District is one of the community service activities carried out by lecturers of the Madura State Islamic Institute and lecturers at Kahuripan Kediri University at Madrasah Ibtidaiyah Al Muhammady Mentoro, Sumobito District, Jombang Regency. This community service activity aims to provide insight and improve teacher competence, especially the development of learning media. The material provided is about several offline and online applications that can be used as a variety of learning media in order to increase interest and motivation to learn, especially during the Covid-19 pandemic. During the Covid-19 pandemic, most and even almost all schools carried out learning from home. So that teachers must be creative and innovative in carrying out learning and providing learning media so that students can continue to learn actively even from home. The method of implementation of this activity is training. Training is carried out by providing / explaining material and carrying out practical activities directly. A lecturer provides material, while other lecturers will accompany the teachers so they don't experience difficulties. Learning media development training as an effort to assist teachers in increasing their knowledge and competence. The result of the training is that teachers can increase their insight and knowledge in terms of developing learning media as shown by the results of making learning media during and after the training.